Only what is necessary: The use of technology in cycling and concerns with its selection and use - Javaloyes, A.; Mateo-March, M. (Journal of Science and Cycling, 2022)
Today, advances in technology, wearables and complex data analysis have revolutionized the world of sports science in general and endurance sports in particular. The fitness-related technology industry has been valued at $100 billion over the past year 2022 and wearable technology tops the ACSM's list of hot topics (Thompson, 2022). A cyclist can generate a huge amount of data just by getting out on the bike and recording their activity with an onboard computer or mobile app. This not only includes data on the exercise itself, such as exercise volume or intensity, but also the relationship between internal and external load, and the role of weather conditions in the physiological response of the athlete. Furthermore, thanks to technology, it is very easy to monitor data outside of training that can influence the adaptive process and the cyclist's performance. Metrics such as heart rate variability or sleep quality are now easy to collect through different wearables (Cao et al., 2022) or even very low-cost mobile apps (Moya-Ramon, Mateo-March, Peña-González, Zabala, & Javaloyes, 2022; Plews et al., 2017).